Effects of 3D-printers and manufacturer-specified post-curing units on the dimensional accuracy, compressive strength, and degree of conversion of resin for fixed dental prostheses - Citra Dewi Sahrir; Wei-Shao Lin; Ching-Shuen Wang; Hwai-En Lin; Chin-Wei Wang; Wei-Chun Lin (Journal of Dental Sciences, 2025)
Background/purpose: The 3D printer and post-curing unit are important factors in producing the best 3D printed crowns. To explore the effects of different combinations of 3D-printers and manufacturer-specified post-curing units on the dimensional accuracy, compressive strength, and degree of conversion (DC%) of 3D-printable resin for fixed dental prostheses. Materials and methods: Specimens were designed in 2 sizes and additively-manufactured using 2 digital light processing (DLP) 3D-printers (NextDent 5100, ND and PrintinDLP+, PN). The 3D-printed samples were polymerized using 2 different post curing units (LC-3D Print box, N and PrintInCure+, P). Dimensional accuracy was evaluated under an optical microscope, while compressive strength was determined using a universal testing machine. Fourier transform infrared spectroscopy was used to analyze the resin molecular bond characteristics and DC%. Statistical analysis, including ANOVA and Tukey's HSD post-hoc tests (P < 0.05). Results: Significant dimensional variations were observed for both square and rectangular samples (P < 0.001). The ND-P showed the greatest ductility and relatively high maximum stress. The fracture strengths were ND-N: 181.55 ± 8.37 MPa, ND-P: 151.54 ± 2.06 MPa, PN-N: 175.51 ± 12.44 MPa, and PN-P: 127.84 ± 10.10 MPa (P < 0.001). Surface inspection at 200 × magnification revealed subtler fault lines in ND-N and PN-P. FTIR analyses confirmed DC% was highest for ND-N (79.70 ± 1.02%) and PN-N (78.12 ± 0.94%), intermediate for ND-P (73.24 ± 0.89%) and PN-P (71.06 ± 1.67%). Conclusion: Post-curing units had a greater impact on dimensional accuracy, strength, and polymerization than the choice of 3D-printer. Optimal resin properties require careful optimization of post-curing parameters and equipment.